2017
DOI: 10.1111/1755-5922.12259
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors of soluble epoxide hydrolase minimize ischemia‐reperfusion‐induced cardiac damage in normal, hypertensive, and diabetic rats

Abstract: Aim We designed a study to evaluate the cardioprotective effect of two soluble epoxide hydrolase (sEH) inhibitors, 1-(1-propanoylpiperidin-4-yl)-3-(4-trifluoromethoxy)phenyl)urea (TPPU) and trans-4-{4-[3-(4-trifluoromethoxyphenyl)-ureido]cyclohexyloxy}benzoic acid (t-TUCB), in ischemia-reperfusion (IR) model. Methods Cardioprotective effects of the sEH inhibitors were evaluated against IR-induced myocardial damage in hearts from normal, hypertensive and diabetic rats using Langendorff’s apparatus. In additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 59 publications
(92 reference statements)
1
11
0
Order By: Relevance
“…Resting tension and developed tension also decreased in the diabetic rat hearts in our study, in line with the findings of Oliul Islam . The decrease in tension may be due to stimulation of β 2 receptors in the heart, resulting in the formation of cAMP through G s ‐protein.…”
Section: Discussionsupporting
confidence: 91%
“…Resting tension and developed tension also decreased in the diabetic rat hearts in our study, in line with the findings of Oliul Islam . The decrease in tension may be due to stimulation of β 2 receptors in the heart, resulting in the formation of cAMP through G s ‐protein.…”
Section: Discussionsupporting
confidence: 91%
“…In our experiment, we observed marginal decrease in hyperglycemia, therefore, the amelioration of memory dysfunction could be due to effect of TPPU on hyperglycemia in addition to its direct effect of on CNS. Microvascular disease [31], and altered cerebral hemodynamic are few of the potential mechanisms [6] responsible for low cerebral blood perfusion and subsequent memory dysfunction in diabetes [13, 32]. Pre-treatment of TPPU to diabetic rat is known to increase the relaxant response of ACh on aorta ex vivo [13] and 5, 6-EET is known to dilate cerebral arterioles [33].…”
Section: Discussionmentioning
confidence: 99%
“…Microvascular disease [31], and altered cerebral hemodynamic are few of the potential mechanisms [6] responsible for low cerebral blood perfusion and subsequent memory dysfunction in diabetes [13, 32]. Pre-treatment of TPPU to diabetic rat is known to increase the relaxant response of ACh on aorta ex vivo [13] and 5, 6-EET is known to dilate cerebral arterioles [33]. Therefore, TPPU also might have ameliorated memory dysfunction by dilating arterioles and increasing blood perfusion in the brain via stabilization of EETs.…”
Section: Discussionmentioning
confidence: 99%
“…These observations imply that cardiomyocyte CYP2J2, and not endothelial CYP2J2, protects the hearts from ischemic-reperfusion injury. In an ex vivo study of rat hearts, treatment with an sEH inhibitor in normal, hypertensive, and diabetic hearts minimized cardiac damage associated with ischemic-reperfusion injury presumably by increasing or maintaining EET levels [ 70 ]. Interestingly, a study by Chaudhary and colleagues [ 84 ] showed that this protection is age-dependent.…”
Section: Cyp2j2 and Cvdmentioning
confidence: 99%